Risk factors association with fathers' persistent psychological distress across the early parenting period - Cooklin, A R; Giallo, Rebecca; Christensen, Daniel; Nicholson, Jan; D'Esposito, Fabrizio (My University, 2013)
One in ten fathers report high levels of psychological distress in the first year after having a baby. However, little is known about the course of distress and associated risk factors beyond the postnatal period. Therefore, the aims of the study were to: a.report on the course of fathers' distress when their children were aged 3-12 months, 2-3 years, 4-5 years, and 6-7 years; b.identify distinct trajectories of distress over time; and c.identify risk factors for persistent distress. Data from 2470 fathers participating in the Longitudinal Study of Australian Children were analysed. Latent growth modelling revealed that for the overall sample, distress was highest in first postnatal year and then decreased over time. Latent class growth modelling identified two distinct trajectories. The majority of fathers (92%) reported moderate distress in the first postnatal year which decreased over time, whilst 8% of fathers reported high distress during the first postnatal year which increased over time. Risk factors for persistent distress were poor relationship quality, low job quality, poor maternal mental health, and low parental self-efficacy. The findings of this study highlight the existence of a group of fathers who experience persistent distress across the early parenting years. Timely interventions to address these difficulties are not only important for promoting the wellbeing of fathers, but also their children and families.
Keywords: Families -- Fathers; Health -- Mental; Families and relationships; Health and wellbeing; Health; Families; Fathers; Mental; Health and wellbeing; Families and relationships